Metamorphosis as a Constitutive Principle of Female Identities in the Works of Boba Blagojević (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes the construction of the female identity as the Other in the collection of stories Sve zveri što su sa tobom (1975). It is focused on the phenomena of transformation, borders and the abject as a constitutive principle in the construction of female characters, as well as on the ontology of absence, tardiness and the permanent inability of representing the female being through the language of the Father. The theoretical platform is provided by the theories of hysteria, melancholy and language by Jacques Lacan and post-Lacanian feminist theorists (Julia Kristeva, Luce Irigaray). The notions of the corporal, the body and bodily transformations are interpreted from the viewpoint of Judith Butler’s and Elizabeth Grosz’s feminist theories of the body.
Keywords: border; abjection; animal; melancholy; metamorphosis